Pranata Hukum Wasiat - Linda Asmaraneti; Reni Puspita; Dwi Noviani; Muyasaroh Muyasaroh (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Many aspects of life are regulated in the Koran, which is the main source of Islamic teachings, including aspects related to wills. In the Qur'an, the word will is often found with different meanings and connotations other than just a message before death. This difference is caused by the use of different will words in the context of the problem. A will is a voluntary gift made by someone to another person, which is made after the death of the giver (testator). Because wills have the nature of worship (human relationship with God), they are also a legal act, a means of getting closer to Allah (taqorrub ilallah) which is often done by many people, especially those who have sufficient wealth. In practice, a will is usually made by someone orally or in writing. This is done so that other people know that this is his will. This research aims to examine the meaning of a will, the reasons for making a will, the wisdom of making a will, the law of wills, the types of wills, the pillars of wills, and the amount of assets that can be bequeathed. The approach used in this research is a qualitative approach with a type of library research. Researchers obtain data from books, journals, articles and others related to the theme or title being discussed.